2020
DOI: 10.1371/journal.pone.0237818
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for mammary structure in Canadian Angus cows

Abstract: Functional and enduring mammary structure is pivotal for producer profitability, and animal health and welfare in beef production. Genetic evaluations for teat and udder score in Canadian Angus cattle have previously been developed. The aim of this study was to identify genomic regions associated with teat and udder structure in Canadian Angus cows thereby enhancing knowledge of the biological architecture of these traits. Thus, we performed a weighted single-step genome wide association study (WssGWAS) to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Among genes found in islands, the TLEA4 gene is crucial for the function of the mammary gland and has previously been reported in Angus cattle by Devani et al [ 60 ]. Additionally, several genes (CFAP61, RALGAPA2, INSM1, and KIZ) were located in a region associated with feed intake, conformation, weight, reproductive traits, and milk production in cattle, as demonstrated by Pitt et al [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among genes found in islands, the TLEA4 gene is crucial for the function of the mammary gland and has previously been reported in Angus cattle by Devani et al [ 60 ]. Additionally, several genes (CFAP61, RALGAPA2, INSM1, and KIZ) were located in a region associated with feed intake, conformation, weight, reproductive traits, and milk production in cattle, as demonstrated by Pitt et al [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the heritability of mammary system-related teat traits of Holstein cattle was of a medium level ( Table 1 ). Previous studies have identified that animal differences in bovine mammary systems are genetically influenced by the heritability value (estimate range between low to medium) [ 1 , 33 ]. Wu et al, 2013, estimated the heritability of front teat placement, teat length and rear teat placement (0.18, 0.21 and 0.11, respectively) in Chinese Holstein cattle [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mammary system traits play an important economic role in cattle [ 1 ]. In dairy cattle, mammary infections are a major problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations